Bioenergia sucroenergética: aspectos da sustentabilidade empresarial - Moraes Júnior, Valdério Freire de (2022)
This research seeks to evaluate, through a multidime nsional trend matrix associated with a web database, the aspects business sustainability of entities o f Brazilian su gar biofuels bioenergy, in period from 2015 to 2020 So, c lassified methodologically as applied research, quali quantitative approach and co mparative method. In addition, the Google Trends (behavior a ssessment through web searches) tool associated with the SWOT matrix (qualitative tool that analyzes elements of strengths, opportunities, weaknesses and elements that contribute for the construction of the thesis product which is a multidimensional standard matrix based on 20 descriptors to g enerate aspects of the business sust ainability of the 61 firms selected in a universe of 422 companies. As a result, the trends were analyzed from li ne graphs and the formula to obtain the average of searches was applied through a file in CSV format. From there, scores (from 1 to 10) and 5 colors (blue, green, yellow, orange and green) were used to assess the sustainable, almost unsustainable, intermed iate, almost unsustaina ble and unsustainable levels to be able to reach the product of this work a multidimensional matrix of referential pattern. Thus, the best scores were obtained within the scale of scores to obtain in the sustainable category the mult idimensional matrix of referential pattern, through the score for Strengths and Opportunities corresponding to the values 9.2 (centralized) and for Weaknesses and Threats equivalent to 0, 8 (laterality) laterality). As results, it was found that the six companies had t he same or approximate level of sustainability in the transition of the best versus worst matrix. Respectively, they were: FS (19% and 20%), Millenium (16% and 18%), Araporã (11% and 11%), Adeco (10% and 11%), Adecoagro (10% and 11%) and Inpasa (7% and 6%) 6%). This ranking reveals that companies switch between the two matrices, depending on factors that lead then to being in a good situation at a given moment and worse in another time . This confirms what was proposed in the theoretical background of this resea rch, that is, there is no constant in the Strengths, Weaknesses , Opportunities and Threats analisys in this context